Production of Triple-Gene (GGTA1, B2M and CIITA)-Modified Donor Pigs for Xenotransplantation - Xu, Kaixiang; Yu, Honghao; Chen, Shuhan; Zhang, Yaxuan; Guo, Jianxiong; Yang, Chang; Jiao, Deling; Nguyen, Tien Dat; Zhao, Heng; Wang, Jiaoxiang; Wei, Taiyun; Li, Honghui; et al. (Frontiers in Veterinary Science, 2022)
Activation of human immune T cells by swine leucocyte antigen class-I and II lead to xenograft destruction. Here, we generated the GGTA1, B2M and CIITA (GBC) triple-gene modified Diannan miniature pigs, analyzed the transcriptome of GBC modified PBMCs in pig spleen and investigated their effectiveness in anti-immunological rejection. Six cloned piglets were successfully generated using SCNT, one of them carrying the heterozygous mutations in triple genes, the other five piglets carrying the homozygous mutations in GGTA1 and CIITA genes, but heterozygous mutation in B2M gene. The autopsy of GBC modified pigs revealed that found that a lot of spot bleeding in kidney, the severe suppuration and necrosis in lung, enlarged peripulmonary lymph nodes and adhesion between the lung and chest wall. Phenotyping data showed that the mRNA expressions of triple genes and protein expressions of B2M and CIITA genes were still detectable and comparable with wild-type (WT) pig in multiple tissues, but α1,3-galactosyltransferase was eliminated, SLA-I was significantly decreased and four subtypes of SLA-II were absent in GBC pigs. In addition, even swine umbilical vein endothelial cells (UVEC) induced by recombinant porcine IFN-γ, the expression of SLA-I in GBC modified pig was lower than that in WT pig. Similarly, the expression of SLA-II DR and DQ also can’t be induced by recombinant porcine IFN-γ. Through RNA-seq, 150 differentially expressed genes were identified in the PBMCs of pig spleen and most of them were involved in immune- and infection-relevant pathways including antigen processing and presentation and viral myocarditis, resulting in the pigs with GBC modification susceptible to pathogenic microorganism. Furthermore, the numbers of human IgM binding to the fibroblast cells of GBC modified pigs were obviously reduced. The GBC modified porcine peripheral blood mononuclear cells (PBMCs) triggered the weaker proliferation of human PBMCs than WT PBMCs. These findings indicated that absence of expression of α1,3-galactosyltransferase and SLA-II and the downregulation of SLA-I enhanced the ability of immunological tolerance in pig-to-human xenotransplantation.